The associations between peak O2 consumption and leptin in 10‐ to 12‐year‐old boys. (3rd April 2013) - Cicchella, Antonio; Stefanelli, Claudio; Purge, Priit; Lätt, Evelin; Saar, Meeli; Jürimäe, Toivo
Summary: The aim of this study was to assess the associations of circulating levels of leptin with the peak O2 consumption (VO2peak ) in 10‐ to 12‐year‐old boys of different BMI selected by Cole et al . (BMJ, 320, 2000, 1–6): total group ( n  =   248), normal ( n  =   190), overweight ( n  =   34) and obese ( n  =   24). We hypothesized that there is a close relationship in overweight and obese subgroups of boys with relative VO2peak kg −1 (ml min −1  kg −1 ) and leptin. Most of the subjects were Tanner stage 2. Peak O2 consumption was measured directly using an increasing incremental protocol until volitional exhaustion on an electronically braked cycle ergometer. The expired gas was sampled continuously breadth‐by‐breadth mode for the measurement of oxygen consumption (MetaMax, Germany). Blood samples were obtained after an overnight fast from an antecubital vein for leptin measurements. Peak O2 consumption (l min −1 ) was higher or lower (ml min −1  kg −1 ) in overweight and obese groups, compared with normal BMI group. Leptin was higher in overweight and obese groups, compared with normal BMI group. Peak O2 consumption (l min −1 ) correlated significantly with leptin only in total group ( n  =   248, r  =   0·196). Contrary, relative VO2peak kg −1 correlated significantly and negatively with leptin. The relationship was highest on the total group ( r  =  −0·674). We can conclude that leptin first of all correlated negatively with relative peak O2 consumption. Absolute VO2peak correlated with leptin only in total group.